Analisis Variabilitas Iklim dan Tren Produktivitas Kelapa Sawit pada Berbagai Zona di Indonesia - Salma Alya' Hanifah; Faustina Yuniastuti; Syalaysa Imani Fatihah; Mutiarra Ridyo Arum; Almira Hafizha Ramadini (Yayasan Literasi Sains Indonesia, 2026)
Climate change poses a significant challenge to the sustainability of palm oil production in Indonesia through changes in rainfall and temperature patterns. This study aims to analyze changes in climate variability and trends in palm oil productivity across various climate zones in Indonesia from 1990 to 2023. The study area encompasses palm oil-producing provinces, grouped into equatorial and monsoon zones based on the BMKG classification. Climate data, including minimum, maximum, and average temperatures, and rainfall, were obtained from NASA Power, while palm oil productivity data were obtained from the Agricultural Statistics Database. The analysis used the Mann-Kendall and Sen's Slope tests to identify the direction and magnitude of change trends, and the Mann-Whitney test to compare climate variability across observation periods. The results show an increasing trend in rainfall and temperature across the study area, indicating wetting and warming phenomena. The equatorial zone has more stable agroclimatic conditions and higher productivity than the monsoon zone. Conversely, the monsoon region experiences thermal stress and higher rainfall fluctuations, potentially reducing productivity. These findings demonstrate the importance of climate adaptation strategies based on agroclimatic zone characteristics to maintain the sustainability of palm oil production in Indonesia.